2014
DOI: 10.1177/0309364613492790
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic factors of vertical jumping for heading a ball in flexible flatfooted amateur soccer players with and without insole adoption

Abstract: Adoption of the insole improved the design of the shoe-foot interface support for the flexible flatfoot athletes, enabling them to develop more effective take-off kinetics for vertical jumping in terms of ground reaction force and stance duration similar to that of normal foot subjects without insole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…However, the reduction in GRF loading was not reported in arch-support insoles for healthy arched subjects in this study, which is partially aligned with the general understanding that with increased rigidity at midfoot/rearfoot by arch-support and/or ankle support, vertical impact loading increased at the early stance phase during running [54] and landing [55]. While external can effectively support the ligamentous structures in reducing overpronation during movements for a more neutral foot alignment [16,23], the kinetic energy originally absorbed by joint motion has to be released through increased impact force [55]. This is in contrast to other studies, which indicated that flatfooted individuals wearing arch-support insoles would experience lower vertical GRF and loading rates at heel contact in landing maneuvers [16].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…However, the reduction in GRF loading was not reported in arch-support insoles for healthy arched subjects in this study, which is partially aligned with the general understanding that with increased rigidity at midfoot/rearfoot by arch-support and/or ankle support, vertical impact loading increased at the early stance phase during running [54] and landing [55]. While external can effectively support the ligamentous structures in reducing overpronation during movements for a more neutral foot alignment [16,23], the kinetic energy originally absorbed by joint motion has to be released through increased impact force [55]. This is in contrast to other studies, which indicated that flatfooted individuals wearing arch-support insoles would experience lower vertical GRF and loading rates at heel contact in landing maneuvers [16].…”
Section: Discussionsupporting
confidence: 82%
“…These injuries may relate to higher level of GRF and joint loading [13,21]. Previous studies have reported that arch-support insoles would provide mechanical support to the medial longitudinal arch of a foot and thus improve postural control and receptor sensory inputs onto the foot plantar in various functional tasks [16,23] and lower risk of knee injuries [21]. However, the reduction in GRF loading was not reported in arch-support insoles for healthy arched subjects in this study, which is partially aligned with the general understanding that with increased rigidity at midfoot/rearfoot by arch-support and/or ankle support, vertical impact loading increased at the early stance phase during running [54] and landing [55].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations